Imagining a Woman's World: Roles for Women in Chinese Films - Rafman, Carolynn (Cinémas, 1993)
Chinese cinema embraces a paradoxical relationship to its own traditions, especially concerning the abusive treatment of women. Films like Yellow Earth, Judou and Raise the Red Lantern which desire to uncover a repressed history, tend instead to reinforce and sustain an image of women's suffering to modern audiences. While exposing discrimination and injustice, some films perpetuate the stigma that women are still second class citizens. Three Chinese women filmmakers have challenged the dominant confusion ethos: "Male honorable, female inferior" (nan zun nü bei) by portraying women as independent and thinking individuals. This article analyses Passion (Zui ai) by Sylvia Chang, Song of the Exile (Ketu qiuhen) by Ann Hui and Three Women (San ge nüren) by Peng Xiaolian.